2020
DOI: 10.3892/etm.2020.9110
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine ameliorates isoflurane‑induced cognitive dysfunction by inhibiting neuroinflammation via miR‑150 in rats

Abstract: Tetramethylpyrazine (TMP) has neuroprotective effects in the pathogenesis of some human diseases, such as Parkinson's disease. The present study aimed to investigate the role of TMP in isoflurane-induced cognitive dysfunction in rats, and further identify the mechanisms involved in the protective effects of TMP. The Morris water maze test was used to evaluate the cognitive function of rats exposed to isoflurane or treated with TMP. ELISA was conducted to evaluate the effects of isoflurane or TMP on neuroinflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Behavioral tests showed that TMP significantly reduced memory impairment of the two AD mouse models. These results are consistent with previous reported studies that TMP can protect against isoflurane-induced cognitive dysfunction in rats (Cui et al, 2020 ) and restore spatial learning and memory impairment in rats injected with streptozotocin (Lu et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Behavioral tests showed that TMP significantly reduced memory impairment of the two AD mouse models. These results are consistent with previous reported studies that TMP can protect against isoflurane-induced cognitive dysfunction in rats (Cui et al, 2020 ) and restore spatial learning and memory impairment in rats injected with streptozotocin (Lu et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…The surgical trauma caused remarkable neurocognitive dysfunction as indicated by our results of OFT and MWM test. It has been reported that isoflurane alone may induce cognitive dysfunction 34,35 . The underlying neurotoxicity of isoflurane include elevating ROS production, inducing neuroinflammation, 36 and disrupting calcium homeostasis 37 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted in rodents have shown that exposure to inhalation anesthetics induces neurodegeneration and impairs memory and cognitive function ( Zhao et al, 2010 ; Komita et al, 2013 ; Fu et al, 2020 ). Isoflurane is commonly used in the clinic ( Kumar et al, 2019 ; Peyton et al, 2020 ; Warren et al, 2020 ), which has also been reported to induces neuroinflammation, neuronal apoptosis, and cognitive impairment ( Cui et al, 2020 ; Neghab et al, 2020 ). Anesthesia and surgery induce systemic inflammatory response and oxidative stress, which could enter the brain through a variety of pathways [either passing directly through the blood brain barrier (BBB) or destroying the BBB] or sending signals to the brain ( Otani and Shichita, 2020 ; Scuderi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%